Relationship between Military-Civilian Transition and Psychological Well-Being, Social Adjustment among Retired Military Personnel in Nigeria - Ruwan, Ibrahim Ignatius Felix; Arobodade, A. A.; Iliya, Vakpa; Ishaya, Dashit Samson (NIU Journal of Social Sciences; Vol 6 No 2 (2020): KIU Journal of Social Sciences, Vol. 6 No. 2, June 2020, 2020)
The paper examined the relationship between Military-Civilian Transition and Psychological Well-being, Social adjustment among retired military personnel in Nigeria. The study adopted a descriptive cross-sectional survey design to sample 119 participants using purposive and convenient sampling method from the five (5) military locations in Nigeria. 8(6.7%) from NDA, 8(6.7%) from 1 Div, 26(21.8%) from Jaji, 55(46.2%) from Kachia resettlement center, 12(10.1%) from Oshodi Lagos resettlement center while 10(8.4%) with no response. 88(73.9%) were Male and 31(26.1%) were Female. Their age ranged from 30-70years with a mean age of 45 and STD age of 65. Their Arms of service are 29(24.4%) were Army, 61(51.3%) were Navy and 29(24.4%) were Air force retired personnel. The military-civilian transition scale, psychological well-being scale and social adjustment scales were used for data collection and were analyzed using Pearson product-moment correlation and regression analysis to test the   hypotheses stated in the study. The results in hypothesis 1 clearly indicated a statistically significant r(117)= -0.473, P< 0.05 moderately negative relationship between Military-Civilian transition and psychological well-being among retired military personnel in Nigeria. Hypothesis two (2) indicated a statistically significant r (117)= -0.266, P< 0.05 negative relationship between military-civilian transition and social adjustment among retired military personnel in Nigeria. Results in hypothesis three (3) also revealed predictor factors influencing psychological well-being of retired military personnel R=0.534; F=9.005, P< 0.05. The predictors also revealed that military-civilian transition ( B= -0.385; t=-4.475, P< 0.01) and social adjustment (B= -0.225; t=2.681, P< 0.01) significantly predicted psychological well-being. While age (B=-0.050; t=-0.593, P> 0, 05). Gender (B=0.093; t=1.072, P > 0.05) and educational status (B=0.00; t-0.026, P > 0.05) do not significantly predict psychological well-being among retired military personnel. Summarily the study found that there is a statistically significant relationship between military-civilian transition and psychological well-being and social adjustment among retired military personnel and also revealed that military-civilian transition and social adjustment as individual predictors of psychological well-being among retired military personnel in Nigeria. Therefore, recommended the establishment of psychological services at all military resettlement and post military barracks to provide psychological diagnoses assessment and treatment of perceived psychological and adjustment disorders.  Keywords:   Military-Civilian, Psychological, Well-being, Social adjustment, Nigeria